Delphi methods as an approach in architecture research: Opportunities and pitfalls (ARTEKS : Jurnal Teknik Arsitektur, 2026)
Participatory approaches hold significant relevance within complex architectural research, serving as a vital link between theoretical inquiry and practical implementation. Among the prominent methods within this paradigm is the Delphi method, a systematic and iterative procedure that employs anonymous expert insights to cultivate collective agreement. While it has long been acknowledged for its strength in producing consensus, forecasting emerging tendencies, filtering conceptual propositions, and assessing issues that demand informed collective judgment, its utilization in architectural research remains comparatively limited. This study seeks to examine the Delphi method’s capabilities, delineate its strengths and constraints, and underscore its prospective contributions to architectural research practices. Employing a qualitative strategy through an integrative review of literature, data were gathered from 54 selected publications issued between 2000 and 2025. These data were subsequently interpreted using thematic content analysis. The results affirmed the Delphi method’s proficiency in generating impartial, multidisciplinary concurrence, its versatility in synthesizing diverse bodies of knowledge, and its particular relevance for navigating complex and future-oriented architectural challenges. Nevertheless, it also encounters obstacles such as participant withdrawal, the possibility of producing manufactured consensus, and inherent limitations in representing real-time social interactions. The methodological potential of the Delphi technique to broaden the boundaries of architectural research becomes even more substantial when combined with approaches such as the Analytic Hierarchy Process, Focus Group Discussions, or Q-Methodology.
Keywords: Architectural research; Delphi methods; Expert consensus; Integrative literature review; Participatory approach